The altered functional connectivity density related to cognitive impairment in alcoholics - Duan, Ranran; Li, Yanfei; Jing, Lijun; Zhang, Tian; Yao, Yaobing; Gong, Zhe; Shao, Yingzhe; Song, Yajun; Wang, Weijian; Zhang, Yong; Cheng, Jingliang; Zhu, Xiaofeng; et al. (Frontiers in Psychology, 2022)
Alcohol use disorders (AUD) is one of the most common substance use disorders, contributing to both behavioral and cognitive impairments in AUD patients. Recent neuroimaging studies point that AUD is a typical disorder featured by altered functional connectivity. However, the details about how largescale functional coordination remains unknown. Here, we adopted a newly proposed method named functional connectivity density (FCD) to depict altered largescale functional coordination in AUD. The novel functional imaging technique –FCD provides a comprehensive analytical method for brain’s “scale-free” networks. We applied resting state functional MRI (rs-fMRI) towards subjects to obtain their FCD, including global FCD (gFCD), local FCD (lFCD) and long-range FCD (lrFCD). 61 AUD patients and 29 healthy controls (HC) were recruited, and the AUD patients were further divided into alcohol-related cognitive impairment group (ARCI, n=11) and non-cognitive impairment group (AUD-NCI, n=50). All subjects were asked to stay stationary during the scan in order to calculate the resting-state gFCD, lFCD and lrFCD values, and further to investigate the abnormal connectivity alterations among AUD-NCI, ARCI and HC.Compared to HC, both AUD groups exhibited significantly altered gFCD in left inferior occipital lobe, left calcarine, altered lFCD in right lingual and altered lrFCD in VMPFC. It is notable that gFCD of ARCI group was found to be significantly deviated from AUD-NCI and HC in left medial frontal gyrus, which change probably contributed by the impairment in cognition. In addition, no significant differences in gFCD were found between ARCI and HC in left parahippocampal, while ARCI and HC were profoundly deviated from AUD-NCI, possibly reflecting a compensation of cognition impairment. Further analysis showed that within AUD patients, gFCD values in left medial frontal gyrus is negatively correlated with MMSE scores, while lFCD values in left inferior occipital lobe positively related with ADS scores. In conclusion, AUD patients exhibited significantly altered functional connectivity patterns mainly in several left hemisphere brain regions, while AUD patients also demonstrated an intergroup FCD differences which correlated with symptom severity, with AUD cognitive impairment patients would suffer less severe alcohol dependence.These findings assisted future AUD studies by providing insight for possible pathological mechanisms.